A Review of C4 Plants in Southwest Asia: An Ecological, Geographical and Taxonomical Analysis of a Region With High Diversity of C4 Eudicots - Rudov, Alexander; Mashkour, Marjan; Djamali, Morteza; Akhani, Hossein (Frontiers in Plant Science, 2020)
Southwest-Asia is climatically and topographically a highly diverse region in the xeric belt of the Old World. The diversity of arid habitats and climatic conditions acted as important factors for the evolution and diversification of up to 20 independent Eudicot C4 origins. Some of these lineages present unique evolutionary strategies like single-cell functioning C4 and C3-C4 switching mechanisms. The high diversity of C4 taxa in Southwest Asia is also related to the presence of seven phytogeographic zones including the Irano-Turanian region as a center of diversification of many Caryophyllales lineages and the Somali-Masai region (Southern Oman and Yemen) as a center of diversification for C4 Monocots. Nevertheless, the C4 flora of Southwest-Asia has not received detailed attention. This paper presents a comprehensive review of all known C4 species in the area based on a literature survey, own floristic observations, as well as taxonomic, phylogenetic and herbarium data, and δ13C-isotope ratio analysis. The resulting checklist includes a total number of 923 (861 native, of which 141 endemic, and 62 introduced) C4 species, composed of 350 Eudicots and 509 Monocots, most of which are therophytic and hemicryptophytic xerophytes with pluriregional and Irano-Turanian distribution. 239 new δ13C-isotope ratios of C4 and C3 plants, as well as some taxonomic changes are presented. An analysis of the distribution of the three main C4 plant families (Chenopodiaceae, Poaceae, and Cyperaceae) in the region in relation to climatic variables indicates that the increase of C4 species follows more or less a latitudinal gradient similar to global patterns, while separate taxonomic groups seem to depend on specific factors as continentality (Chenopodiaceae), average annual temperature (Cyperaceae) and the presence of summer precipitation (Poaceae). An increase of C4 Eudicots in W-E direction even in similar longitudinal belts is explained by a combination of edaphic and climatic conditions. The provided data should encourage a deeper interest in the evolution of C4 lineages in Southwest-Asia and their adaptation to ecological and climatical conditions and awaken interest in the importance of local C4 crops, the conservation of threatened C4 taxa and awareness of human impacts on the rapid environmental changes in the region.